Game-based Learning in Technology Management Education: A Novel Business Simulation - Günther, Markus; Kiesling, Elmar; Stummer, Christian (International Journal of Emerging Technologies in Learning (iJET), 2011)
Management games allow students to obtain valuable first-hand experience that is of particular value in a field such as technology management, which usually involves substantial risk as well as significant time lags between a managerial decision and its effects. In drawing from more than fifteen years of experience with management games in higher education, we have developed a management simulation for teaching technology management, a field that is increasingly regarded an important area of study for engineering students. This paper outlines a blended-learning design for a course on technology management, describes the various didactical elements as well as their effects in class, and addresses the technical implementation of the management game as a service-oriented multi-tier application in Java.